PENANAMAN PENDIDIKAN MULTIKULTURAL MELALUI MODEL PEMBELAJARAN MODIFIKASI TINGKAH LAKU PADA MATA PELAJARAN IPS (STUDI KASUS SMP MUHAMMADIYAH 5 KAYEN, KABUPATEN PATI, JAWA TENGAH) - Sulaswari, Misroh (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
Multicultural Education Planning Through The Behavior Modification Learning Model In Social Studies Subjects (Case Study Of SMP Muhammadiyah 5 Kayen, Pati District, Central Java). The purpose of this study is to instill multicultural education through behavioral modification learning models in social studies subjects especially for students who are in religious-based schools. Multicultural education is the process of developing all human potential that respects its plurality and heterogeneity as a consequence of cultural, ethnic, racial and religious diversity. The focus of this study is how teachers provide multicultural education through behavioral modification learning models to students. The purpose of multicultural education itself is to prepare students with a number of knowledge, attitudes, and skills needed as an effort to develop cultural awareness. The behavior modification learning model, better known as behaviorism, is any effort made to change the behavior of certain individuals. With behavior modification the teacher is expected to focus on changing student behavior and understanding why or how such behavior can occur. This study uses a mixed qualitative quantitative approach with a type of field research. The method used was experimental without the control class by giving some stimulus in the form of interactive videos and pictures of various cultures in Indonesia intensively during social studies learning within one semester. After giving the stimulus, it was known that a positive response emerged from students in the form of multiculturalism, which amounted to 93% and the remaining 7% gave a neutral / apathetic response.Keyword:Multicultural Education, Learning Model, Behavior Modification